Pengaruh Literasi Keuangan, Akses Permodalan, Motivasi, dan Minat menggunakan E-Commerce terhadap Kinerja UMKM di Kabupaten Buleleng - Komang Agem Wismanjaya; Desak Nyoman Sri Werastuti (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of financial literacy, access to capital, motivation, and interest in using e-commerce on the performance of UMKM. This research is a type of quantitative research. The sample was determined using the Slovin formula with an error rate of 10% so that the number of respondents was 89 UMKM actors in Buleleng Regency who already had a Small and Medium Business License (IUMK). Data was obtained by distributing questionnaires using google form media. The data used is primary data in the form of respondents' answers and processed using SPSS version 20. The results of this study indicate that financial literacy, access to capital, motivation, and interest in using e-commerce have a positive effect on the performance of UMKM in the Buleleng Regency. The better financial literacy, access to capital, motivation, and interest in using e-commerce, the better the performance of UMKM in Buleleng Regency.